Sweet-1: 1st Ever Sweet Corn Open Pollinated Variety in Punjab Pakistan - Hussain, Aamir; Murtaza, Ghulam; Akbar, Waseem; Ghani, Aamir; Yousaf, Muhammad Irfan; Shehzad, Aamar; Parveen, Najma; Ibrar, Iqra; Ali, Barkat; Suleman , Gohar; et al. (Biological and Clinical Sciences Research Journal, 2025)
Sweet corn (Zea mays L. var. saccharata) is a specialty type of maize primarily consumed after roasting. Despite its growing demand, its cultivation remains limited in Pakistan, and no officially approved sweet corn variety has been available for general cultivation. The development of a high-yielding, disease-resistant variety is crucial to reducing import dependency and enhancing local production. Objective: To develop and evaluate a high-yielding, disease-resistant sweet corn variety suitable for general cultivation in Pakistan, focusing on its agronomic performance, disease resistance, and yield potential. Methods: The variety Sweet-1 was developed through recurrent selection from the base population Yusafwala Pool-30, undergoing five selection cycles for enhanced grain yield and quality traits. The variety was assessed in station trials and National Uniform Maize Yield Trials across Pakistan, comparing its performance with a local landrace. Agronomic evaluations were conducted to determine optimal planting conditions during the Kharif and spring seasons. Resistance to Fusarium moniliforme (stalk rot) was tested over two growing seasons. Statistical analyses were performed to compare yield differences between Sweet-1 and the check variety. Results: Yield Performance: Sweet-1 exhibited a 28% higher yield in station trials and a 10% higher yield in national trials compared to the check variety.Disease Resistance: The variety demonstrated moderate resistance to stalk rot (Fusarium moniliforme), showing stable performance across two seasons. Agronomic Optimization: Kharif season: Best results were obtained with row-to-row spacing of 75 cm and plant-to-plant spacing of 15 cm. Spring season: Plant-to-plant spacing of 17.5 cm was found to be optimal for maximum grain yield. Conclusion: The approval and adoption of Sweet-1 will provide a high-quality sweet corn variety for general cultivation in Pakistan. Its higher yield potential, disease resistance, and optimized agronomic practices will contribute to enhanced local production, reducing reliance on imports and lowering the import bill.